Oral communication needs in the ICT industry - Mohd Noor, Zainab; Sarudin, Isarji (2014)
In recent years, employers have reiterated the need for graduates to be proficient in oral communication in English so that they can function effectively in the workplace. Although oral communication skills in English have been an integral component of the undergraduate course syllabus, there appears to be little research on the oral communication needs in the ICT industry. The objective of the paper is to present the findings of a study to investigate workplace oral communication needs in the ICT industry in terms of oral communication functions, contexts, interaction patterns and assessment criteria. The study employed quantitative research design using a 21-item survey questionnaire. A total of 31 employers in the ICT industry participated in this study. Based on the overall findings of the study, interaction patterns of oral communication skills were perceived the least important, followed by assessment criteria, contexts and functions.